2009
DOI: 10.1359/jbmr.090603
|View full text |Cite
|
Sign up to set email alerts
|

Fra-1/AP-1 Impairs Inflammatory Responses and Chondrogenesis in Fracture Healing

Abstract: Inflammation inevitably follows injury of various tissues, including bone. Transgenic overexpression of Fra-1, a component of the transcription factor activator protein-1 (AP-1), in various tissues progressively and globally enhances bone formation, but little is known about the possible effects of Fra-1/ AP-1 on fracture healing. We created a transverse fracture of the mouse tibial diaphysis and examined fracture healing radiologically, histologically, and immunologically. Strikingly, fracture union was delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
(75 reference statements)
0
16
0
Order By: Relevance
“…Because bone formation is enhanced in Fra-1 Tg mice (9, 12, 19), we separately analyzed the healing process after tibial transverse fracture and consistently found that production of inflammatory cytokines, including TNF-a and IL-6, around the bone fracture site is impaired in these mice (20). Furthermore, using the murine macrophage cell line RAW264.7 overexpressing Fra-1 by rentivirus, Morishita et al (21) reported that Fra-1 negatively regulates LPS-induced production of TNF-a, IL-1, IL-6, and NO.…”
Section: Discussionmentioning
confidence: 97%
“…Because bone formation is enhanced in Fra-1 Tg mice (9, 12, 19), we separately analyzed the healing process after tibial transverse fracture and consistently found that production of inflammatory cytokines, including TNF-a and IL-6, around the bone fracture site is impaired in these mice (20). Furthermore, using the murine macrophage cell line RAW264.7 overexpressing Fra-1 by rentivirus, Morishita et al (21) reported that Fra-1 negatively regulates LPS-induced production of TNF-a, IL-1, IL-6, and NO.…”
Section: Discussionmentioning
confidence: 97%
“…Fra-1 has been shown to be a negative regulator of proinflammatory cytokine production in a murine macrophage cell line and in mouse models of colitis and bone fracture, presumably through inhibiting NFkB activity (Morishita et al, 2009;Yamaguchi et al, 2009;Takada et al, 2010). Overexpression of the closely related Fos family member Fra-2 (encoded by Fosl2) induces pulmonary fibrosis .…”
Section: Discussionmentioning
confidence: 99%
“…Given the reduced production of major proinflammatory cytokines seen in Fra-1 mice (Yamaguchi et al, 2009;Takada et al, 2010), we asked whether Fra-1 mice might be resistant to inflammatory responses induced by LPS. Surprisingly, when Fra-1 mice and littermate wild-type controls were injected i.p.…”
Section: Fra-1 Enhances Lps-induced Interstitial Lung Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…11 The observation of increased chemokine production in Fra-1 transgenic mice was not anticipated, since these mice show reduced inflammatory responses in bone and the intestinal tract. 13,14 That Fra-1 differentially modulates Tnfa and Ccl2 expression is further supported by the observation that mice lacking Fra-1 do not show skewed expression of cytokines and chemokines and are resistant to gefitinib/LPS-induced lung injury. 11 In addition, inhibition of MCP-1 by neutralizing antibody or a small-molecule inhibitor against its receptor partially prevents lung injury.…”
Section: Introductionmentioning
confidence: 90%